2023
DOI: 10.1371/journal.pgen.1010694
|View full text |Cite
|
Sign up to set email alerts
|

The defense island repertoire of the Escherichia coli pan-genome

Abstract: It has become clear in recent years that anti-phage defense systems cluster non-randomly within bacterial genomes in so-called “defense islands”. Despite serving as a valuable tool for the discovery of novel defense systems, the nature and distribution of defense islands themselves remain poorly understood. In this study, we comprehensively mapped the defense system repertoire of >1,300 strains of Escherichia coli, the most widely studied organism for phage-bacteria interactions. We found that defense syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…Finally, we identified a third defence-hotspot encoded between LptG and a GTPase. We note that the protein annotated as GTPase is homologous to YjiA, a protein that, together with YjiO, defines the boundaries of a defence island in Escherichia coli 17 . Unlike E. coli , we did not find YjiO homologues in S. marcescens strains (Figure 1c and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we identified a third defence-hotspot encoded between LptG and a GTPase. We note that the protein annotated as GTPase is homologous to YjiA, a protein that, together with YjiO, defines the boundaries of a defence island in Escherichia coli 17 . Unlike E. coli , we did not find YjiO homologues in S. marcescens strains (Figure 1c and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The 590 high-quality bacterial genome assemblies were subjected to a prophage sequence search using PHASTER (35). A total of 2595 prophage-like sequences were detected in nearly all genomes analyzed, except for P. syringae pv.…”
Section: Resultsmentioning
confidence: 99%
“…For other plant-associated bacteria specifically, this number has been shown to be as high as 10 mechanisms for some Ralstonia and Xanthomonas isolates (34). In sharp contrast to other bacterial species (35,36), and even other Pseudomonads, CRISPR-Cas does not appear to be an important phage defense strategy in the P. syringae species complex (37,38). Instead, we demonstrated that P. syringae relies on other defense mechanisms, such as restriction enzymes and abortive infection strategies, to cope with phage predation.…”
Section: Discussionmentioning
confidence: 99%
“…PPs are prolific agents of horizontal gene transfer, including implications in the spread of antibiotic resistance 39,85 . The spread of genetic content between bacteria within the gut may have dramatic effects on human health in terms of increased bacterial virulence, persistence, and antibiotic resistance 85,86 . Due to their higher levels of accessory genes and larger genomes there is more room for genome plasticity and genetic exchange without disrupting essential gene functions in PPs.…”
Section: Discussionmentioning
confidence: 99%